vanstuk / offtrack. - Nieuwe Vide, Haarlem (Haarlem : Nieuwe Vide Haarlem, 2005)
Fontijne, Yvonne ; Voskuil, Jan Maarten ; van der Ploeg, Jan ; Ligteringen, Hans ; de Rooij, Marie Jeanne ; Ron-Wontae Kim ; Visser, Kees ; Schenk, Menno ; B.O.S.C.H. ; Mühlenbruch, Nils ; Koster, Guda ; Dijkstra, Anno ; Postma, Pieter W. ; Stooker, Yarre ; Sandberg, Martijn ; van Tartwijk, Frans ; Redundant Technology Initiative ; Fokkema, Pietsjanke ; Geesin, Dan ; Broersen, Persijn ; Lukacs, Margit
Engels, Nederlands
Exhibition. Hosted II. Nieuwe Vide Haarlem. 2005-06-05. 2005-07-03
boek